Determinantes do desempenho financeiro das cooperativas de crédito singulares no Brasil - Prolo Júnior, Carlos Damião (Universidade do Vale do Rio dos Sinos, 2019)
The dissertation purpose is to investigate the determinants of the financial performance of the credit unions in Brazil and to test whether the revenues diversification and mergers has a positive impact on the financial performance of credit cooperatives. To do so, the sample was divided into two research groups, observing the operations practiced. Group 1 consists of full credit unions and traditional credit unions and group 2 is composed of capital and loan credit unions. Using data from 2010 to 2017 and applying the fixed-effects model, we found evidence that the determinants common to the financial performance of credit unions, as measured by the ROA and ROE, for the two groups are: higher-level efficiency, lower level of credit operations, lower level of loan portfolio provision and lower degree of leverage. Still for group 1 is a determinant of the financial performance a higher level of the relation between services revenues / administrative expenses and a greater size of the credit union. For Group 2 a lower level of revenue diversification is a determining factor.
Keywords: Fatores determinantes; Desempenho financeiro; Cooperativa de crédito; Determinants factors; Financial performance; Credit union; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis